2000
DOI: 10.1002/j.2048-7940.2000.tb01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Keys to Bowel Success

Abstract: Although many rehabilitation clients have neurogenic bowels requiring special bowel protocols, a review of the literature affirmed the authors' assumptions and experiences as professional nurses that any bowel program must begin with a good nursing assessment, a clean bowel, and eight keys to success. Once these criteria are met, bowel care can be individualized to meet the needs of the specific patient. This article presents a review of the literature and provides references for nurses seeking additional info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Böhmer et al (2001) note that until research provides clear answers as to how to manage constipation in people with intellectual disabilities, the basic principles for treatment are the same for individuals with intellectual disabilities as for the general population. As a basic principle, it has been suggested that bowel management should begin with the "eight keys to bowel success" prior to developing an individualised bowel programme: physical exercise, high fibre intake, high fluid intake, consistent habit time, an upright position on toilet or commode, privacy, medication management, and patient and family education (Weeks, Hubbartt, & Michaels, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Böhmer et al (2001) note that until research provides clear answers as to how to manage constipation in people with intellectual disabilities, the basic principles for treatment are the same for individuals with intellectual disabilities as for the general population. As a basic principle, it has been suggested that bowel management should begin with the "eight keys to bowel success" prior to developing an individualised bowel programme: physical exercise, high fibre intake, high fluid intake, consistent habit time, an upright position on toilet or commode, privacy, medication management, and patient and family education (Weeks, Hubbartt, & Michaels, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…8,15 In rehabilitation centres, nurses care for the bowel management of patients with SCI and initiate a bowel management program. 21 The aim of such programs is to eliminate faecal incontinence or other complications 3,19 and to evacuate stool at a regular, predictable time 14,19 within 60 min. 7 The interventions include the manual removal of stool 11,15,17,19,22 for patients with an areflexic bowel as well as techniques like digital stimulation 11,15,22 and suppositories 11,15,22 for patients with a reflexic bowel to initiate reflex peristalsis, 14 frequency, 14 timing of bowel evacuation, 11,22 and the usage of oral laxatives.…”
Section: Introductionmentioning
confidence: 99%
“…() note that until research provides clear answers as to how to manage constipation in people with intellectual disability, the principles for treatment are the same for individuals with intellectual disability as for the general population. As a basic principle, it has been suggested that bowel management should begin with the “eight keys to bowel success” prior to developing an individualized bowel programme: physical exercise, high fibre intake, high fluid intake, consistent habit time, an upright position on toilet or commode, privacy, medication management, and patient and family education (Weeks, Hubbartt, & Michaels, ). Whilst early studies on constipation management for people with intellectual disability focused on specific elements of constipation management (e.g., dietary fibre), a recent study considers the management of constipation using abdominal massage in the context of a total bowel management programme (Connor et al., ).…”
Section: Discussionmentioning
confidence: 99%